ANALISA CACAT LAS (CRACK) PADA JOINT BUTT WELD PENGARUH DARI PENGELASAN CRANE PEDESTAL PADA PROJECT WTIV (WIND TURBINE INSTALLATION VESSEL) - Sutijo, Bambang; Hilmy, Zakwan; Adi, Fajar Tyas; Susilo, Trisno (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2025)
Wind farm transportation installation vessel (WTIV) is a vessel specifically designed to install offshore wind turbines. Most are self-elevating jack up rigs. To enable rapid relocation at the wind farm, the power plan is self during the process fabrication block, a cracked weld defect was found visually in one of the butt weld joints. The amount of support resulting from calculating the influence of the load from the crane pedestal is 494 kpa in the deck plate area where cracks were found to be defective and this can influence the occurrence of cracks in the butt joint. Meanwhile, the maximum stress calculation that can be calculated due to the crane pedestal load is σ: 0.370 N/mm2 or σ: 370Mpa on the deck plate. Meanwhile the steps to repair the welding crack so that it doesn’t happen again, what must be done is by adding support under the deck crane pedestal, while is terms of welding repair that is by carrying out welding in accordance with the WPS and welding sequence.